Discontinuities in understanding follicular development, the ovulatory cycle and the oviposition cycles in the hen: Advances, opportunities, slow downs and complete stops - Scanes, Colin G. (Frontiers in Physiology, 2022)
There has been considerable progress in understanding follicular development, the ovulatory cycle and the oviposition cycles in the hen. In particular, there have been tremendous advances in understanding follicular development and recruitment of follicles to the hierarchy of large yellow follicles. There is a need to continue to follow the earlier literature while employing present techniques. Early work allowed an understanding of the ovulation and oviposition cycles. Models for ovulation were developed. However, while these have no passed the test of time, there is no present model that fully accounts to the cycles. Earlier work employed ahemoral light cycles to examine ovulation and oviposition cycles. Recent work has demonstrated that clock genes are expressed in the ovary. The control of incubation by prolactin has been largely elucidated in turkeys. There is evidence that other endocrine glands influence female reproduction in birds including the adrenal cortex, thyroid and pineal. However, there is much that remains to be fully understood.